2014
DOI: 10.1002/mabi.201400226
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Honeycomb as Nests for Controlled Osteoblast Spatial Organization

Abstract: Honeycomb nanofibrous scaffolds were elaborated by electrospinning onto micro-patterned collectors either with poly(ϵ-caprolactone) (PCL) or poly(D, L-lactic acid) (PLA). The unimodal distribution of fiber diameters, observed for PLA, led to relatively flat scaffolds; on the other hand, the bimodal distribution of PCL fiber diameters significantly increased the relief of the scaffolds' patterns due to the preferential deposition of the thick fiber portions on the walls of the collector's patterns via preferent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 37 publications
0
27
1
Order By: Relevance
“…The use of multiple spinnerets can accelerate the throughput of the process, [81,82] although care must be taken to avoid interfering electric fields; even then, the production rate of porous materials is still slower than some other methods. Furthermore, micropatterned collectors can be designed to obtain aligned porous scaffolds containing both micro/macropores and a nanofibrous structure without requiring additional control or postprocessing steps; [39,83] gradients in both the radial direction and the longitudinal direction can also be directly incorporated into the macroporous hydrogel by designing appropriate mandrel-based collectors. [84,85] The main drawback of electrospinning is the stability of the resulting macroporous networks (particularly under pressure) given that there are typically no bonds between the fibers themselves, making them relatively easy to compress.…”
Section: Electrospinningmentioning
confidence: 99%
“…The use of multiple spinnerets can accelerate the throughput of the process, [81,82] although care must be taken to avoid interfering electric fields; even then, the production rate of porous materials is still slower than some other methods. Furthermore, micropatterned collectors can be designed to obtain aligned porous scaffolds containing both micro/macropores and a nanofibrous structure without requiring additional control or postprocessing steps; [39,83] gradients in both the radial direction and the longitudinal direction can also be directly incorporated into the macroporous hydrogel by designing appropriate mandrel-based collectors. [84,85] The main drawback of electrospinning is the stability of the resulting macroporous networks (particularly under pressure) given that there are typically no bonds between the fibers themselves, making them relatively easy to compress.…”
Section: Electrospinningmentioning
confidence: 99%
“…In another set of experiments, we studied the adhesion and growth of human keratinocytes on nanofibrous membranes made of poly-ε-caprolactone (PCL) and its copolymer with PLA (PLA/PCL, ratio 70:30). PCL and PLA/PCL copolymers have been experimentally used for vascular tissue engineering, particularly for replacement of small caliber blood vessels [31,32], neural tissue engineering, specifically for generation of conductive sheaths for neurite outgrowth [104], for substituting the dura mater [105], and also for bone tissue engineering in order to mimic hemi-osteons and to control the spatial organization of osteoblasts [106]. These applications of PCL and PLA/PCL were enabled, among others, by suitable mechanical properties of these polymers, particularly in case of PLA/PCL.…”
Section: Nanofibers In Skin Tissue Engineeringmentioning
confidence: 99%
“…1a-c). Such electrostatic template has been used to control the deposition of the up-coming electrospun jet and produce 2D 11,20 or even 3D 13,14 patterned scaffolds. Thus, thanks to this electrostatic template effect, it was possible to control very precisely the deposition of electrosprayed hydroxyapatite (HA) microparticles.…”
Section: Electrostatic Template-assisted Deposition (Etad)mentioning
confidence: 99%
“…16,17 Finally, it has been demonstrated that the topography of the electrospun scaffold has got an important inuence on the cell behavior. [18][19][20] Electrospun membranes have been incorporated in biochips allowing biological experimentations in individual micro-wells having a bottom with non-structured randomly deposited nanobers. [21][22][23] However, to the best of our knowledge, nobody reported the elaboration of biochips allowing cell culture for a wide range of micropatterned nanobrous structures.…”
Section: Introductionmentioning
confidence: 99%